The Magnolia story - Gaines, Chip. 1974-; Gaines, Joanna, 1978-; Dagostino, Mark (Nashville, Tennessee : W Publishing Group, an imprint of Thomas Nelson, 2016)
The Magnolia Story is the first book from Chip and Joanna, offering their fans a detailed look at their life together. From the very first renovation project they ever tackled together, to the project that nearly cost them everything; from the childhood memories that shaped them, to the twists and turns that led them to the life they share on the farm today.
Keywords: Gaines, Chip, -- 1974-; Gaines, Joanna, -- 1978-; Fixer upper (Television program); Television personalities -- Texas -- Biography; Businesspeople -- Texas -- Biography; Dwellings -- Remodeling -- Texas -- Biography